An investigation into intercultural components in three piloted English textbooks for Vietnamese high schools under National Foreign Language 2020 project - Kiều, Thị Hà (2020)
In order to seek the answer to whether English textbooks under the national project 2020 launched by the Ministry of Education and Training foster ICC,the study sets out to investigate intercultural components and the learning tasks presented in the textbooks. With a view toenhancingstudents‟ ICC, it is important that textbooks should provide inputs as well as practice for students to develop all dimensions of ICC knowledge, attitudes and skills.Therefore, the research also aims at investigatingintercultural elements and the dimensionsof intercultural communicationcompetencethat the learning tasks in the textbooksaddress. The results of the study can be a reference for teachers for appropriate adaptation and adjustment of the material to suit their teaching contexts as well as to meet their students‟ needs.The research will try to find the answer for the following questionsto serve above-mentioned objectives: What proportionsof interculturalcomponentscan be found in the analyzed textbooks? What dimensions of intercultural communicationdo the learning tasks in thosetextbooks address?